Plant extracellular vesicles and their potential in human health research, the practical approach - Kocholata, M; Maly, J; Martinec, J; Auer Malinska, H (Physiological research, 2022)
Extracellular vesicles are small membrane particles (30-1000 nm) released by Bacteria, Eukaryotes and Archaea. They have been shown to play an important role in intracellular and intercellular communication, within and between kingdoms via transport of bioactive molecules. Thus, they can be involved in altering gene expression and regulation of physiological and pathological processes of the recipient. Their unique properties make extracellular vesicles a perfect candidate vector for targeted drug delivery or a biomarker. For a long time, animal and mainly mammal extracellular vesicles have been used in research. But for plants, there had been speculations about the existence of nanovesicles due to the presence of a cell wall. Today, awareness of plant extracellular vesicles is on the rise and their research has proved they have various functions, such as protein secretion, transport of bioactive molecules or defense against pathogens. Further potential of plant extracellular vesicles is stressed in this review.
Keywords: Biomarkers; Extracellular Vesicles; savci; Bacteria; Drug Delivery Systems; extracelulární vezikuly; biologické markery; Animals; lidé; Mammals; Humans; lékové transportní systémy; zvířata; mezibuněčná komunikace; Cell Communication